Predicative Attributes According to Āyatullāh Jawādī Amulī - Mustafā Sultānī (حکمت اسرا)
The issue of predicative attributes (al-Òifāt al-khabarīyya ) entered the realm of theology and Qur’anic interpretation alongside the descent of revelation. In the understanding of the predicative verses and how these attributes have been ascribed to God, such views as anthropomorphism (tashbīh) and tajsīm (affirmation without“esoteric interpretation” ta’wīl), suspension (tawaqquf) and delegation (tafwīÃ), affirmation without quality, affirmation with ta’wīl, have been attributed to theologians and Quranic commentators. The above-mentioned views developed in response to the question that how God has described Himself by predicative attributes while ascription of such attributes to Him requires attribution of non-divine qualities (anthropomorphism, tajsim, …) to Him. Āyatullāh Jawādī Amulī tries to reply to this question by holding the view of “affirmation with ta’wīl”, taking the theory of “identity of attributes and essence” and the principle of “transcendence” (tanzīh) as the basis of interpretation of predicative attributes. He realizes and interprets predicative attributes by referring the ambiguous verses (mutashābihāt) to the explicit verses (muÎkamāt), showing superiority of demonstrative reason over the appearances of Islamic traditions, and using the verbal and confirmative signification (al-dilālat al-lafÛiyya wa al-taÒdīqīyya).